2014
DOI: 10.1155/2014/461935
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Delays in Tuberculosis Diagnosis and Treatment Services: Does Gender Matter?

Abstract: Background. Tuberculosis (TB) remains a global public health problem with known gender-related disparities. We reviewed the quantitative evidence for gender-related differences in accessing TB services from symptom onset to treatment initiation. Methods. Following a systematic review process, we: searched 12 electronic databases; included quantitative studies assessing gender differences in accessing TB diagnostic and treatment services; abstracted data; and assessed study validity. We defined barriers and del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
74
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 102 publications
5
74
1
Order By: Relevance
“…25 Stigma among women of TB has been one proposed source of these gender discrepancies. 9,26,27 In some settings, women with TB are more likely to conceal their disease, 28,29 are at risk for social and community isolation, 28,30 or are not screened for TB by health-care professionals despite having TB symptoms. 31 Causes for these gender differences, specifically in Nanjing, China, should be further investigated through qualitative studies.…”
Section: Discussionmentioning
confidence: 99%
“…25 Stigma among women of TB has been one proposed source of these gender discrepancies. 9,26,27 In some settings, women with TB are more likely to conceal their disease, 28,29 are at risk for social and community isolation, 28,30 or are not screened for TB by health-care professionals despite having TB symptoms. 31 Causes for these gender differences, specifically in Nanjing, China, should be further investigated through qualitative studies.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the influence of gender on other correlative factors has not been found, and it is almost same with Yang's review on quantitative studies assessing gender differences in accessing TB diagnostic and treatment services. 23 What is more, health insurance and awareness of policy have positive impact on active health seeking behavior, which shows that medical security and less/free policy have significant meaning to TB prevention and cure. Li's study on delay of initial health-seeking in new pulmonary tuberculosis cases among migrants population in East China concluded that interventions to improve health seeking behavior among the migrant population in China must focus on strengthening their labor, medical security and health education.…”
Section: Discussionmentioning
confidence: 99%
“…However, the scope note associated with this descriptor is “Care that is sensitive to sex-specific needs. General only; consider also MEN’S HEALTH and WOMEN’S HEALTH”,36 further demonstrating the lack of clear differentiation between sex and gender.…”
Section: Introductionmentioning
confidence: 99%
“…Stigma is often gendered with blame and shame apportioned to women and can result in isolation and psychosocial consequences for women which, in turn, affect access to care and health outcomes 20,24. Although the gendered social consequences of TB are, therefore, context specific, they compound, exacerbating each other, resulting in individuals experiencing different forms of delay (access and referrals) to complete lack of access to medical care 22,36…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation